Three airports - Asadov, Alexander; Asadov, Andrey (project baikal, 2021)
The airport terminals in Perm, Saratov and Kemerovo created by Asadov Architectural bureau are presented. General concepts of complexes, architectural and interior solutions for passenger terminals, as well as elaboration of design codes of administrative and technical buildings are given. Particular attention is paid to passenger comfort and safety.
Keywords: airport terminals; Perm; Saratov; Kemerovo; design code; technical characteristics; structures; techniques